2011
DOI: 10.1111/j.1750-3841.2011.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Edible and Medicinal Plants in Inhibition of Growth, Adherence, and Cytotoxin Production of Campylobacter jejuni and Campylobacter coli

Abstract: Innovative tools for controlling Campylobacter, such as natural products from plants, represent good alternatives for use in foods or as therapeutic agents. The extracts of Acacia farnesiana, Artemisia ludoviciana, Opuntia ficus-indica, and Cynara scolymus were the most effective against these microorganisms. Adherence and cytotoxic activity of the bacteria to host mucosal surfaces which are critical steps in pathogenesis were decreased by these extracts. Our results point to these plants as potential candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…Mucilage levels affect the pH of the medium, but an alteration in acidity seems not to be sufficient to change microbial growth or volatile fatty acid production. Although a few studies consider that the spineless-cactus mucilage has some substances with antimicrobial activity (CASTILLO et al, 2011;SANCHÉZ et al, 2010), based on the present results, no indications of such type of activity were observed on the rumen microorganisms. Inclusion of spineless-cactus mucilage levels in the in vitro system affects the pattern of fermentation of starch, cellulose, and protein performed by rumen microorganisms.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…Mucilage levels affect the pH of the medium, but an alteration in acidity seems not to be sufficient to change microbial growth or volatile fatty acid production. Although a few studies consider that the spineless-cactus mucilage has some substances with antimicrobial activity (CASTILLO et al, 2011;SANCHÉZ et al, 2010), based on the present results, no indications of such type of activity were observed on the rumen microorganisms. Inclusion of spineless-cactus mucilage levels in the in vitro system affects the pattern of fermentation of starch, cellulose, and protein performed by rumen microorganisms.…”
Section: Resultscontrasting
confidence: 55%
“…There are many studies about the potential effects of the antimicrobial activity of spineless-cactus mucilage on several microorganisms associated with the intestinal tract of animals, which is an object of interest in the pharmaceutical area. Castillo et al (2011) observed a bactericide effect of cactus mucilage on the growth of Campylobacter jejuni and Campylobacter coli, whereas Sánchez et al (2010) saw its bactericidal effect on Vibrio cholerae. However, this bactericidal effect was not found on the rumen microorganisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dilution method according to Castillo, Heredia, Contreras, and García (2011), with minor modifications was carried out. Briefly, an aliquot (50 μL) of fresh cultures adjusted to McFarland standard (0.5 ≈ 1 × 10 8 ) of each strain were added separately in tubes containing 5 mL of MHB with various concentrations of AN, LN, 5×, 10×, 20× (0.25, 0.5, 1.0, 1.5, 2, 2.5 mg/mL final concentration in each tube for every oil).…”
Section: Determination Of Minimum Inhibitory Concentration (Mic) and mentioning
confidence: 99%
“…For centuries, medicinal plants have been used in traditional medicine to treat a wide range of diseases including digestive disorders such as ulcers. Aqueous extract of thyme and ethanolic extract of cinnamon have anti H. pylori effects [11][12][13].…”
Section: Introductionmentioning
confidence: 99%